2017
DOI: 10.52317/ehj.v2i1.212
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesiapsiagaan Perawat Dalam Memberikan Pelayanan Kegawatdaruratan Sistem Pernafasan Akibat Bencana Alam Di Wilayah Kerja Dinas Kesehatan Kabupaten Deli Serdang

Abstract: Preparedness and complete alertness is one of the important elements of activities in reducing the risk and the impact of disaster. The same is true to nurses’ preparedness and complete alertness in providing emergency service in respiratory system which is urgently needed during the disaster immediate responsiveness. Quick and accurate service can help and save victims from physical defect and death Goal: The objective of the research was to know the condition of nurses’ preparedness and complete alertness in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…Synthesis of research articles that have the main focus of discussion, namely (1) research, (2) methods, (3) samples, (4) results, and (5) research conclusions. The intervention used was based on sources, namely the use of modules according to national and international standards (Kalanlar, 2018); K3 and MFK programs (Samosir, R. V., Suroto, S., & Kurniawan, 2015); evaluation instruments (Arrigoni et al, 2017); Education and training (Sonneborn et al, 2018); (Lestari & Priambodo, 2017); and Basic Life Support and Basic Traumatic Coronary Life Support (Simbolon & Situmorang, 2017).…”
Section: Chart 1 Flowchart Of Article Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of research articles that have the main focus of discussion, namely (1) research, (2) methods, (3) samples, (4) results, and (5) research conclusions. The intervention used was based on sources, namely the use of modules according to national and international standards (Kalanlar, 2018); K3 and MFK programs (Samosir, R. V., Suroto, S., & Kurniawan, 2015); evaluation instruments (Arrigoni et al, 2017); Education and training (Sonneborn et al, 2018); (Lestari & Priambodo, 2017); and Basic Life Support and Basic Traumatic Coronary Life Support (Simbolon & Situmorang, 2017).…”
Section: Chart 1 Flowchart Of Article Selection Processmentioning
confidence: 99%
“…In addition, based on the research of Simbolon & Situmorang, (2017), it was found that there are three most important domains owned by nurses in providing services in emergency conditions, namely the domains of knowledge, attitudes, and skills. From the study result, it was found that most nurses had knowledge in the good category and the category of positive attitude, but there were still some nurses who were not skilled in carrying out emergency actions.…”
Section: Disaster Education Program For Nursesmentioning
confidence: 99%
“…Pengetahuan merupakan salah satu komponen dari kompetensi petugas kesehatan termasuk perawat. 10,11,12 Sejalan pula dengan Hasil penelitian yang dilakukan oleh Ajmain (2013), dimana hasil penelitiannya menunjukkan bahwa perawat yang terlibat dalam tim penanggulangan bencana di wilayah kerja Dinas Kesehatan Aceh Tamiang mayoritas memiliki pengetahuan yang baik yaitu 65,0%, sedangkan yang memiliki pengetahuan sedang 20,0%, hanya 15% responden yang memiliki pengetahuan kurang, berdasarkan skor jawaban responden manyoritas perawat pengetahuannya baik yaitu 78%. Penelitian yang dilakukan oleh Cut (2017), menyatakan bahwa faktor yang mempengaruhi kesiapsiagaan bencana terdiri dari 1) faktor pengetahuan terhadap kesiapsiagaan bencana, 2) sikap terhadap kesiapsiagaan bencana, 3) kebijakan dan panduan, 4) rencana untuk keadaan darurat bencana, 5) sistim peringatan bencana, dan 6) mobilisasi sumber daya.…”
Section: Pembahasanunclassified
“…Padahal, keterampilan atau skill merupakan keahlian yang harus di miliki oleh seseorang untuk melakukan pekerjaanya dalam bidang tugasnya masing-masing. 12 Faktor yang mempengaruhi kesiapsiagaan perawat diantaranya adalah kemampuan kognitif, sikap (afektif), dan psikomotor (skill) dalam disaster manajemen. 14,15 Peningkatan kemampuan dan keterampilan dapat dilakukan melalui pelatihan terkait, pelatihan yang dilakukan secara kontinyu akan membuat seseorang terampil, sehingga keterampilan yang dimiliki terkait penanggulangan bencana dapat dipergunakan jika saja sewaktu-waktu dibutuhkan.…”
Section: Pembahasanunclassified
“…Pemahaman materi ini dapat meningkatkan kesiapsiagaan bencana yang menganggu sistem pernapasan manusia yang diakibatkan oleh bencana alam maupun non alam seperti kabut asap kebakaran hutan, gunung meletus. Bencana ini bisa menganggu jalan pernapasan manusia seperti masuknya partikel debu, cairan dan gas yang beracun pada saluran pernapasan (Simbolon and Situmorang 2017).…”
unclassified